Arthroscopic Subscapularis Tendon Repair Using a Transpectoral Viewing Portal - F. Okke Lambers Heerspink, M.D., Ph.D.; Alexandra M. Leenders, M.D.; Freek Hollman, M.D., Ph.D. (Arthroscopy Techniques, 2025)
The subscapularis is the strongest muscle in the rotator cuff and is essential for shoulder function and stability. Arthroscopic repair of the subscapularis tendon can be challenging as the result of muscle retraction, the proximity of the axillary nerve, and impaired visualization. In some cases, a 70° arthroscope is required to enhance the tendon view. We describe the use of a transpectoral viewing portal to facilitate arthroscopic repair of subscapularis tears.